Changing patterns of general practice services during a period of public sector investment in Britain - Motab Aljohani; Michael Donnelly; Ciaran O’Neill (PLoS ONE, 2025)
Introduction Given the importance of GP care to the public’s health, it is important that we understand how patterns of service use change as levels of investment change. This study investigated GP use in Britain in conjunction with use of outpatient services during a period of investment and during a period of austerity. Method The study used data from the British Household Panel Survey (BHPS) that included service use, morbidity (as an indicator of need) and socio-demographic characteristics (e.g., employment, age, education, and sex). Data for 2000, 2004, and 2008, were specifically chosen for comparison with data from 2015, 2016 and 2017. Service use and respondent characteristics were described using measures of central tendency and dispersion. Multivariable analyses were undertaken using recursive bivariate probit (RBVP) and probit analyses separately for each study year. All analyses were adjusted for cross-sectional weighting. Results BHPS respondents who used outpatient services or GP services had higher morbidity compared to survey participants who did not. Older people, people with lower educational attainment and employed people had higher mean morbidity indices in each study year as did females. Morbidity among service users tended to decline slightly over time. RBVP analyses revealed a significant positive correlation in residuals between outpatient and GP functions in 2000 and 2004 but not 2008. GP consultations and outpatient use remained largely unrelated to socio-economic factors in each year. Survey participants who reported hearing or vision impairment conditions were consistently less likely to use GP or outpatient services in 2000 and 2004, in 2008. Conclusion The results are broadly indicative of stable relationships in service use during a period of healthcare investment but change during austerity. Those who reported, vision, hearing, and skin conditions were consistently less likely to report use of GP or outpatient services, controlling for other aspects of health.